Beyond tradition : contemporary Indian art and its evolution - Jacka, Jerry D.; Jacka, Lois Essary (Flagstaff, Ariz. : Northland Pub., 1988)
A splendid study of modern Indian art. Clara Lee Tanner introduces the book with an essay on the tradition. Lois Jacka describes the artists and their powerful work. Jerry Jacka has made extraordinarily fine photos that have been printed expertly by Dai Nippon.
Includes index.
National Cowboy & Western Heritage Museum Western Heritage Award for art book, 1989.
105328
Keywords: Geschichte 1950-1985; 1900-1999; Indian art -- 20th century; Indian art -- North America -- 20th century; Art, American -- 20th century; Kunst; Bildband; Nordamerika